Regional integration in Africa bridging the North - Sub-Saharan divide (pretoria Africa Inst South Africa, 2011)
Regional Integration in Africa Bridging the North-Sub-Saharan Divide came about as a research project conducted by the Africa Institute of South Africa and examines the North African countries' strategies of involvement in the African continent, and their integration initiatives. The book looks at major issues involving Egypt, Libya, Tunisia, Algeria, Morocco and Mauritania. These countries, in most cases, have been treated as separate from sub-Saharan Africa. However, the historical reality and economic and political interests indicate that the North African countries have been and still are closely connected with the rest of the African continent. Egypt, for example, was one of the leading countries in the African unity movement, and, together with Libya, has contributed to the restructuring of the African continental organisation and the establishment of the African Union. The book consists of two parts. The first part includes five chapters written in English, the second part of the book comprises six chapters written in Arabic.
Includes bibliographical references.
Keywords: Regional economics -Africa.